Safe and Productive Application of Hydraulic Backhoes in Coal-Bearing Areas of Complex Structured Deposits; Geotechnical and Geological Engineering; Vol. 35, iss. 5 - Tyulenev M. A. Maksim Anatolievich; Zhironkin S. A. Sergey Aleksandrovich; Litvin O. I. Oleg Ivanovich; Tyuleneva E. A. Ekaterina Aleksaedrovna; Zhironkina O. V. Olga Valerjevna; Markov S. O. Sergey Olegovich (2017, 2017)
Title screen